EFEKTIVITAS MODEL PEMBELAJARAN PQ4R TERHADAP HASIL BELAJAR MATAPELAJARAN EKONOMI SMA PANCA BHAKTI PONTIANAK - Eku, Emerensiana; Warneri, Warneri; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the effectiveness of the PQ4Rlearning model on the Economic learning outcomes of class XI Panca Bhakti High School Pontianak. The method used in this study is an experimental method with a pre-experimental design research design with the design used is one group pretest posttest design. The population in this study were all students of class Xl IPS Panca Bhakti High School Pontianak. Based on the final data results, it can be concluded that there is a significant influence after using the PQ4R learning model in the economics class Xl Panca Bhakti High School Pontianak. Specifically, it can be described as follows: (1) The average score of students before using the PQ4R model is 51.57 with a percentage of completeness of 19.23%. (2). The average score of students after using the PQ4R learning model is 72.61 with a percentage of completeness of 65.39% with the medium category. (3) Effective use of the PQ4R learning model for economic learning outcomes in class Xl Panca Bhakti High School Pontianak by using paired sample t-testÂ that is t-count value of -93 with probability (sig) 0.001.Â Keywords : PQ4R (Preview, Question, Read, Reflect, Recite, Review) Learning Model, Learning OutcomesÂ